2016
DOI: 10.1007/s11274-016-2083-7
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of propagation of Bacopa monnieri (L.) from hairy roots, elicitation and Bacoside A contents of Ri transformed plants

Abstract: Agrobacterium rhizogenes mediated transformation has been experimented in leaf explants of the memory herb Bacopa monnieri in order to assess the regeneration potential of hairy roots (HR) followed by the elicitation of transformed plants for increased Bacoside A production. Out of the four strains tested, A4 and MTCC 532 derived HR exhibited regrowth in MS basal medium while MTCC 2364 derived HR showed regeneration in MS medium supplemented with suitable phyto hormones. R1000 derived HR possessed no regenerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Several researchers have established Ri-transformed roots and plants following A. rhizogenes infection in B. monnieri and demonstrated the effect of T-DNA genes on growth, biomass accumulation and bacosides production in transformed tissues (Majumdar et al 2011;Bansal et al 2014;Paul et al 2015;Largia et al 2016). However, few attempts were made on A. tumefaciens mediated transformation where hygromycin/ kanamycin resistant transgenic plants expressing GUS gene were produced to develop an e cient protocol in this species (Ramesh et al 2011;Mahender et al 2012;Aggarwal et al 2013;Yadav et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several researchers have established Ri-transformed roots and plants following A. rhizogenes infection in B. monnieri and demonstrated the effect of T-DNA genes on growth, biomass accumulation and bacosides production in transformed tissues (Majumdar et al 2011;Bansal et al 2014;Paul et al 2015;Largia et al 2016). However, few attempts were made on A. tumefaciens mediated transformation where hygromycin/ kanamycin resistant transgenic plants expressing GUS gene were produced to develop an e cient protocol in this species (Ramesh et al 2011;Mahender et al 2012;Aggarwal et al 2013;Yadav et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Establishment of hairy root culture and Ri-transformed plant regeneration from Ri-transformed roots following A. rhizogenes mediated genetic transformation have been reported in B. monnieri which highlighted the stimulatory role of T-DNA genes on secondary metabolite production (Majumdar et al 2011;Bansal et al 2014;Paul et al 2015). Spontaneous shoot regeneration was noted either directly or from dedifferentiated Ri-transformed calli in growth-hormone free basal medium in Ri-transformed root explants but not in control non-transformed root explants (Majumdar et al 2011;Paul et al 2015;Largia et al 2016). This suggests that Ri-transformed roots have higher competence to undergo shoot organogenesis due to the regulation of morphogenic pathways in transformed tissues by T-DNA oncogenes specifying auxin and cytokinin synthesis.…”
Section: Introductionmentioning
confidence: 98%
“…[21], and Ipomoea purpurea (L.) Roth [22]. However, Largia et al [26] also found that an increased concentration and an increased period of exposure to chitosan had a negative effect on the growth of Bacopa monnieri (L.). Nonetheless, the medium with lower chitosan concentration, Chit100, allowed obtaining similar plants as in the control medium.…”
Section: Resultsmentioning
confidence: 99%
“…Chitosan, a linear polysaccharide derived from chitin, is a very versatile biomaterial, when comparing to other natural and synthetic polymers [18]. This biopolymer has been used to improve plant growth [19][20][21][22] and seed germination [21,23], as an elicitor of secondary metabolites [24][25][26], and as a disinfectant agent [27]. Conventionally, agar, a natural polysaccharide, is used to solidify in vitro plant culture media due to its gelling properties, stability, resistance to plant metabolic enzymes and high clarity [28].…”
Section: Introductionmentioning
confidence: 99%
“…As saponins usually occur in plants in very low levels, substantial amounts of biomass would be required to obtain large quantities of the drug. An alternative could be obtaining saponins in biotechnological processes (Largia, Satish, Johnsi, Shilpha, & Ramesh, 2016) or by chemical semisynthetic routes (Yang, Laval, & Yu, 2014); however, current technologies require definite improvements for mass-scale production.…”
Section: Limitations Of Saponins In Therapymentioning
confidence: 99%